Technological Properties of Model System Beef Emulsions with Encapsulated Pumpkin Seed Oil and Shell Powder - Slaviša Stajić; Ana Kalušević; Igor Tomasevic; Biljana Rabrenović; Anđelija Božić; Petar Radović; Viktor Nedović; Dušan Živković (Polish Journal of Food and Nutrition Sciences)
The aim of this research was to examine the technological properties of beef emulsions in which fatty tissue was partially substituted with pumpkin seed oil (PSO) encapsulated in alginate or pectin matrix, and where phosphates (F treatments) were simultaneously substituted with shell powder (C treatments). Fat replacement (in the amount of 25%) mostly had no significant influence on pH, cooking loss, purge loss, fluid release under pressure, residual nitrite level, and texture properties. On the other hand, higher yellowness and hue angle were observed when backfat was replaced with encapsulated PSO, but only in treatments with phosphates. The use of shell powder as a phosphate replacer led to significantly higher pH values and thus to significantly higher residual nitrite level: 70.87–74.64 mg/kg (C treatments) vs . 56.79–62.16 mg/kg (F treatments). The nitrite depletion rate during the seven-week storage was lower in C treatments. Moreover, higher lightness, yellowness and hue angle could be expected, as well as lower hardness, springiness, cohesiveness and chewiness. For the most part, seven-week storage had no influence on the observed technological properties, except on colour properties in which an opposite trend was observed in terms of yellowness – increase in treatments with phosphates and decrease in treatments with shell powder. Further research, which would include sensory analysis, should be conducted to determine how these altered colour and textural properties will be perceived by consumers.